KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN SEJARAH DI SMA ISLAM AL-FALAH KOTA JAMBI - Anggraini, Lisa (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2020)
AbstractPedagogical competence of history subjects at Al-Falah Islamic University in Jambi City, namely: (1) Ability to make learning plans, including: a) Able to plan the organization of learning materials, such as being able to explore and describe the material listed in the curriculum, able to choose materials teaching in accordance with the material, able to use adequate learning resources. b) Able to plan the management of learning to be achieved according to competence, have a suitable type of strategy / learning method, determine learning steps, determine ways that can be used to motivate students. c) Able to plan the use of media and facilities that can be used to facilitate the achievement of competencies. d) Able to plan learning model assessment models, such as determining forms, procedures, and assessment tools. (2) The ability to implement learning with indicators, among others: a) Able to apply basic teaching skills, b). Able to apply various types of approaches, strategies and learning methods. c) Able to master the class.Keywords: Pedagogical Coordination, History Subject TeacherAbstrakKompetensi pedagogik guru mata pelajaran sejarah di SMA Islam Al-Falah Kota Jambi yaitu : (1) Kemampuan dalam membuat perencanaan pembelajaran, antara lain : a) Mampu merencanakan pengorganisasian bahan pembelajaran, seperti mampu menelah dan menjabarkan materi yang tercantum dalam kurikulum, mampu memilih bahan ajar yang sesuai dengan materi, mampu menggunakan sumber belajar yang memadai. b) Mampu merencanakan pengelolaan pembelajaran yang ingin dicapai sesuai kompetensi, memiliki jenis startegi/metode pembelajaran yang cocok, menentukan langkah-langkah pembelajaran, menentukan cara yang dapat digunakan untuk memotivasi peserta didik. c) Mampu merencanakan penggunaan media dan sarana yang bisa digunakan untuk mempermudah pencapaian kompetensi. d) Mampu merencanakan model penilain proses pembelajaran, seperti menentukan bentuk, prosedur, dan alat penilain. (2) Kemampuan pelaksanaan pembelajaran dengan indikator, antara lain : a) Mampu menerapkan keterampilan dasar mengajar, b). Mampu menerapkan berbagai jenis pendekatan, strategi dan metode pembelajaran. c) Mampu  menguasai kelas.Kata kunci: Kopetensi Pedagogik, Guru Mata Pelajaran Sejarah